A Standardized Scale to Measure the Attitude of Farmers Towards Zero-Till Drill (Indian Journal of Extension Education, 2021)
A measurement instrument has been developed that can used to determine the attitude of farmers towards the use of zero-till drill in agriculture. Likert’s summated rating scale technique was followed for the construction of the attitude scale. A total of 28 statements concerning experts’ opinions were selected. Response for the selected statements was obtained from 100 adopter farmers of zero-till drill in Punjab state. The scale developed finally consisted of 13 items including positive and negative items. Three constructs were identified regarding zero till technology in the scale developed, obtained by using exploratory factor analysis. The reliability and validity of the scale indicate its precision and consistency of the results. The developed scale can be used to explore the attitude of farmers towards zero-till drill, which will be helpful to enhance the adoption of this conservation practice.